Expression of South East Asian Ovalocytic Band 3 Disrupts Erythroblast Cytokinesis and Reticulocyte Maturation - Flatt, Joanna F.; Stevens-Hernandez, Christian J.; Cogan, Nicola M.; Eggleston, Daniel J.; Haines, Nicole M.; Heesom, Kate J.; Picard, Veronique; Thomas, Caroline; Bruce, Lesley J. (Frontiers in Physiology, 2020)
Southeast Asian Ovalocytosis results from a heterozygous deletion of 9 amino acids in the erythrocyte anion exchange protein AE1 (band 3). The report of the first successful birth of an individual homozygous for this mutation showed an association with severe dyserythropoietic anaemia. Imaging of the proband’s erythrocytes revealed the presence of band 3 at their surface, a reduction in Wr(b) antigen expression, and increases in glycophorin C, CD44 and CD147 immunoreactivity. Immunoblotting of membranes from heterozygous Southeast Asian Ovalocytosis red cells showed a quantitative increase in CD44, CD147 and calreticulin suggesting a defect in reticulocyte maturation, as well as an increase in phosphorylation at residue Tyr359 of band 3, and peroxiredoxin-2 at the membrane, suggesting altered band 3 trafficking and oxidative stress, respectively. In vitro culture of homozygous and heterozygous Southeast Asian Ovalocytosis erythroid progenitor cells produced bi- and multi-nucleated cells. Enucleation was severely impaired in the homozygous cells and reduced in the heterozygous cells. Large internal vesicular accumulations of band 3 formed, which co-localised with other plasma membrane proteins and with the autophagosome marker, LC3, but not with ER, Golgi or recycling endosome markers. Immunoprecipitation of band 3 from erythroblast cell lysates at the orthochromatic stage showed increased interaction of the mutant band 3 with heat shock proteins, ubiquitin and cytoskeleton proteins, ankyrin, spectrin and actin. We also found that the mutant band 3 forms a strong interaction with non-muscle myosins IIA and IIB, while this interaction could not be detected in wild type erythroblasts. Consistent with this, the localisation of non-muscle myosin IIA and actin was perturbed in some Southeast Asian Ovalocytosis erythroblasts. These findings provide new insights toward understanding in vivo dyserythropoiesis caused by the expression of mutant membrane proteins.